Hypertension knowledge, preventive behaviors, and primary care integration among patients at Medan Johor Community Health Center - Aqila Amelia Afni; Pahala Maringan Jubel Simangunsong; Hartono Hartono (Buletin Kedokteran & Kesehatan Prima, 2026)
Background: Hypertension is a non-communicable disease that can lead to serious complications if not managed properly. Patients' knowledge level is hypothesized to influence their preventive behaviors, particularly within the context of Primary Care Integration (Integrasi Layanan Primer, ILP) implemented at community health centers. This study aimed to determine the relationship between knowledge level and preventive behaviors for hypertension complications among patients in the ILP program at Medan Johor Community Health Center.  Method: A quantitative survey design was used. Data were collected in April–May 2026 using printed questionnaires. The population comprised 7,648 hypertension patients, with a sample of 99 respondents determined using the Slovin formula and purposive sampling. Univariate and bivariate analyses (Chi-square test) were performed. Results: Most respondents were aged 55–64 years (53.5%), female (69.7%), had senior high school education (59.6%), and were housewives (62.6%). The majority had good knowledge (72.7%) and good preventive behaviors (90.9%). The Chi-square test showed a p-value of 0.669 (p > 0.05), indicating no significant relationship between knowledge level and preventive behaviors for hypertension complications in this population. Conclusion: Although most hypertensive patients had good knowledge and good preventive behaviors, knowledge was not significantly associated with preventive behavior in the context of ILP implementation. Other factors such as family support, motivation, and healthcare access may play more influential roles.